Dimensional change of acrylic resin plate after the reinforcement of glass fibre - Dwiyanti Feriana Ratwita; Rinda Mahalistiyani (Faculty of Dental Medicine, Universitas Airlangga https://fkg.unair.ac.id/en, 2007)
The effect of fibre reinforcement of polymethyl methacrylate was investigated. Glass fibres have been studied as strengthening material added to polymethyl methacrylate. The purpose of this study was to evaluate dimensional change of acrylic resin plate after glass fibre reinforcement. As a research subject is an acrylic resin plate of 65 × 10 × 2.5 mm with the number of 32 samples were distributed randomly in 4 experimental groups. Each group consisted of 8 samples and control groups. Group 1: acrylic resin plate and 1 sheet glass fibre; group 2: acrylic resin plate and 2 sheet glass fibre; group 3: acrylic resin plate and 3 sheet glass fibre. Control group which was not given treatment. Dimensional change was measured by profile projector. The data was analyzed by One-Way ANOVA and LSD test showed that there was significant difference in dimensional change (p < 0.005). The conclusion suggested that dimensional change of the acrylic resin plates after glass fibre reinforcement minimally done 1 sheet glass fibre.